Hepatitis D: A still relevant disease. (March 2023) - Battistella, S.; D'Arcangelo, F.; Grasso, M.; Zanetto, A.; Senzolo, M.; Germani, G.; Gambato, M.; Cillo, U.; Gringeri, E.; Vitale, A.; Burra, P.; Russo, F.P.
Abstract : Introduction: Hepatitis D virus (HDV) affects approximately 5% of chronically infected hepatitis B (HBV) patients and remains a common indication for liver transplantation (LT), which is the only therapeutic option for patients with end-stage liver disease and unresectable hepatocellular carcinoma (HCC). Aim: Our aim was to investigate the different characteristics, indications to LT and long-term patient survival of HDV-coinfected patients compared to HBV-monoinfected patients. Matherials & Methods Results: All patients waitlisted for LT at our Center between 2006 and 2020 were retrospectively evaluated. Demographic characteristics, indication to LT, liver function, type of antiviral therapy before and after LT were recorded. A total of 1555 patients were included in the waiting list (WL): 18.2% of patients were HBsAg positive of which 32.6% were HDV-coinfected. At the time of admission to WL, HBVD patients differed significantly from HBV-monoinfected patients in terms of gender (females 42.4% vs 14%, p<0.001), and age (54, IQR 45 – 56 vs. 56, IQR 51 – 61, p=0.017). HDV-coinfected patients had significantly lower rate of HCC diagnoses (36/92 – 22% vs 128/192 – 66%, p<0.001) and HCC as indication to LT (21/92 – 17.2% vs 101/192 – 52.6%, p<0.001). Patients with HBVD had similar probability to LT (65.7% vs 64.7%, OR 1.046 CI95% 0.5-2.3, p=0.9) and death (21% vs 19%, OR 1.13 CI95% 0.5-2.8, p=0.8) than monoinfected patients, but they were less often excluded from WL due to stability of disease (1% vs. 5%). HBVD patients had similar patient survival (p=0.981) as HBV-monoinfected patients. Post-transplant prophylaxis was based on combination therapy with NUCs and HBIG. HDV-coinfected patients did not experience viral relapse after LT. Conclusions: Hepatis D infection is still significantly prevalent among HBsAg carriers. LT is the only curative approach for end-stage liver disease. Survival after LT was comparable to that of HBV-monoinfected patients.